The Role of the Intelkam Unit of Blitar Police in Implementing Early Detection of Social Conflicts Due to Forest Function Change (Advances in Police Science Research Journal, 2024)
Illegal logging at the start of the reformation made forestry land in the South Blitar area barren. The process of cooperation between Perhutani and the community to improve forests and also provide benefits to residents has in fact not been successful due to the fact that currently the majority of forest areas in South Blitar have been turned into sugar cane land. This research focuses on the implementation of early detection and the role of the Blitar Police Intelligence and Security Unit in preventing social conflict as a result of forest conversion. This research uses descriptive qualitative methods, and data collection is carried out through observation, interviews and document study. Testing the validity of the data uses triangulation of sources, techniques, time and theory. The results of the research show that there are still obstacles in implementing early detection, especially in organizing and implementing activities which are still not in accordance with the provisions and products issued and the quality and quantity of personnel from the Blitar Police Intelligence and Security Unit is not sufficient. From the research that has been carried out, it can be concluded that the early detection activities of the Blitar Police Intelligence and Security Unit cannot be said to be optimal because there are still several processes or steps that have not been implemented properly.
Keywords: PERAN SATUAN INTELKAM POLRES BLITAR DALAM MELAKSANAKAN DETEKSI DINI KONFLIK SOSIAL DAMPAK PENGALIHAN FUNGSI HUTAN